2015
DOI: 10.5539/ijel.v5n6p66
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Use of Lexical Chunks by Chinese EFL Learners in Writing

Abstract: . AbstractLexical Approach put forward by Michael Lewis (1993) is widely acknowledged in EFL teaching and lexical teaching is very important development in the evolution of language teaching (Lowe, 2003). For about thirty years of teaching English as a foreign language (EFL) in China, more and more teachers have realized the importance of teaching and encouraging learners to use ready-made lexical chunks. However, the present study focuses on the overuse of lexical chunks in learners' writings in a high stake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Unfortunately, it is now widely acknowledged that second/foreign language learners demonstrate great difficulty generating native-like and appropriate formulaic sequences (e.g., Gómez Burgos, 2015;Xu and Zhang, 2015;Shi and Wang, 2015;Chen and Baker, 2010). This leads to drastic effects on their production, particularly in writing, as their poor use of formulaic sequences may lead to increased and sustained processing burdens for readers (e.g., Millar, 2001), notable differences than native speakers' academic discourse (e.g., Dontcheva-Navratilova, 2012) and lower scores in composition classes (e.g., Ohlrogge, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is now widely acknowledged that second/foreign language learners demonstrate great difficulty generating native-like and appropriate formulaic sequences (e.g., Gómez Burgos, 2015;Xu and Zhang, 2015;Shi and Wang, 2015;Chen and Baker, 2010). This leads to drastic effects on their production, particularly in writing, as their poor use of formulaic sequences may lead to increased and sustained processing burdens for readers (e.g., Millar, 2001), notable differences than native speakers' academic discourse (e.g., Dontcheva-Navratilova, 2012) and lower scores in composition classes (e.g., Ohlrogge, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when learners received collocation instruction, their reading comprehension promoted. In the same vein, Shi and Wang (2015) conducted a study on lexical chunks preferred by Chinese learners in their writings and indicated Chinese EFL learners trust more functional lexical chunks in writing but their chunk variety is fairly limited.…”
Section: Resultsmentioning
confidence: 99%
“…In the study conducted by Shi and Wang (2015), it was aimed to find out the lexical chunks preferred by Chinese learners in their writings and indicated what they mean by the overuse of lexical chunks. For the purpose of producing a list of refined lexical chunks, the key criterion of the length and frequency thresholds was four-word lexical chunks occurring three times or more.…”
Section: Introductionmentioning
confidence: 99%